Peritubular Capillaritis in Native Kidney Biopsies. Issue 3 (26th May 2022) - Sarioglu, Sulen; Tekin, Emel; Unlu, Mehtat; Yildiz, Serkan; Heybeli, Cihan
Abstract: Objectives: To determine the frequency and predictors of peritubular capillaritis (PTCitis) among native kidney biopsies. Methods: Consecutive native kidney biopsies of 169 patients were reexamined for capturing possible PTCitis according to the Banff Classification. The relation of PTCitis with demographic and clinicopathologic findings was evaluated. Logistic regression analysis was performed to determine predictors of PTCitis. Results: Peritubular capillaritis was captured in 90 (53.3%) patients, with scores of 1, 2, and 3 in 57 (33.7%), 31 (18.3%), and 2 (1.2%) patients, respectively. The highest frequency of PTCitis was observed in pauci-immune glomerulonephritis. In univariate analysis, male sex, the presence of interstitial inflammation, pauci-immune glomerulonephritis, and a higher serum creatinine level were associated with a higher risk of PTCitis, while severe interstitial fibrosis/tubular atrophy was associated with a lower risk. The presence of interstitial inflammation (odds ratio [OR], 5.94 [95% confidence interval (CI), 1.41-25.03]; P = .015), pauci-immune glomerulonephritis (OR, 3.08 [95% CI, 1.01-9.36]; P = .048), and a higher serum creatinine level (per 1 mg/dL) (OR, 1.56 [95% CI, 1.14-2.11]; P = .005) were independent predictors of PTCitis development in a multivariate regression model. Conclusions: Peritubular capillaritis is common in native biopsies and more likely to be observed in the presence of interstitial inflammation, pauci-immune glomerulonephritis, and a higher serum creatinine level.